IL GENERE APHELESIA (RHYNCHONELLIDA, BRACHIOPODA) NEL MIO-PLIOCENE ITALIANO (Rivista italiana di Paleontologia e Stratigrafia, 2020)
The three species of Aphelesia recognized in the Miocene and Pliocene of Italy are here revised. All descriptions are based also on topotypic material, the primary types being lost. They are Aphelesia bipartita (Brocchi, 1814) from the Pliocene of Castellarquato (Piacenza) Reggio Calabria area, Aphelesia margineplicata (Philippi, 1844) ( = A. plicatodentata Costa, 1 852, junior synonym) from the Upper Miocene of Francavilla and Pizzo Calabro (Catanzaro), Aphelesia pseudobipartita (Sacco, 1902) from the Pliocene of Rivarone (Alessandria). Basic statistics complete the taxonomic study. The main palaeoecological factors are also discussed. Aphelesia seems to be bounded to the circalittoral stage, on sandy or calcarenitic bottoms. Usually is associated with the genus Terebratula and bryozoans, except for A. pseudobipartita from Rivarone (Alessandria).